UNDERINVESTIGATED ROLES OF GLUCOSE-6-PHOSPHATE DEHYDROGENASE - Dmytro Gospodaryov (Vasyl Stefanyk Precarpathian National University, 2015)
The review examines certain aspects of the reaction catalyzed by glucose-6-phosphate dehydrogenase (G6PDH) in living organisms of different taxa, from bacteria to humans. Particular emphasis is put to the role of G6PDH in iron homeostasis and lipogenesis. Prooxidant and antioxidant roles of G6PDH are also highlighted along with several currently known mechanisms of G6PDH regulation.